1985
DOI: 10.1083/jcb.100.1.18
|View full text |Cite
|
Sign up to set email alerts
|

Glycoprotein 115, a glycoprotein isolated from chick blood vessels, is widely distributed in connective tissue.

Abstract: An extracellular glycoprotein (gp 115) with an apparent Mr = 115,000 isolated from chick aortas (Bressan, G. M., i. Castellani, A. Colombatti, and D. Volpin, 1983, J. Biol. Chem., 258:13262-13267), was used to immunize mice. The antisera were shown to specifically recognize gp 115 by numerous criteria: a major band around Mr = 115,000 plus minor bands of lower Mr were visible by immunoblotting on aorta extracts, and a similar pattern was observed with a monoclonal antibody; no cross-reactivity was detected by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 23 publications
2
29
0
Order By: Relevance
“…This group is shared by two Elastin microfibril interface-located proteins, designated as EMILIN-1 and EMILIN-2, and multimerin, a massive, soluble protein found to be expressed in platelets, megakaryocytes, and vascular endothelium (24). Unlike EndoGlyx-1, EMILINs are expressed in connective tissues of blood vessels, skin, heart, lung, kidney, and cornea (25)(26)(27). EndoGlyx-1 p125/p140 diverges in domain architecture from EMILIN-1 and multimerin by a short cluster of charged amino acids located in the transition between the coiled-coil and the C1q-like domains.…”
Section: Identification Of Endoglyx-1 48591mentioning
confidence: 99%
“…This group is shared by two Elastin microfibril interface-located proteins, designated as EMILIN-1 and EMILIN-2, and multimerin, a massive, soluble protein found to be expressed in platelets, megakaryocytes, and vascular endothelium (24). Unlike EndoGlyx-1, EMILINs are expressed in connective tissues of blood vessels, skin, heart, lung, kidney, and cornea (25)(26)(27). EndoGlyx-1 p125/p140 diverges in domain architecture from EMILIN-1 and multimerin by a short cluster of charged amino acids located in the transition between the coiled-coil and the C1q-like domains.…”
Section: Identification Of Endoglyx-1 48591mentioning
confidence: 99%
“…In a previous study, we showed that mice deprived of EMILIN1, an ECM multidomain glycoprotein, presented an abnormal lymphatic phenotype with a significant reduction of anchoring filaments, lymphatic vessel hyperplasia, and a mild lymphatic dysfunction (28). EMILIN1 (Elastic Microfibril Interface Located proteIN) is associated with elastic fibers (29) and besides being expressed in lymphatic capillaries, it is particularly abundant in the walls of large blood vessels (30), intestine, lung, lymph nodes, and skin (28). EMILIN1 interacts with the a4b1 integrin through its gC1q domain, and it has strong adhesive and migratory properties for different cell types (31)(32)(33).…”
Section: Introductionmentioning
confidence: 99%
“…Several components that contribute to the elastic fiber organization have been identified and cloned, including microfibril-associated proteins 1 to 4 (3-6), latent transforming growth factor ␤-binding proteins 1 to 4 (7-10), fibulins 1 and 2 (11,12), microfibril-associated glycoprotein-2 (13), and EMILIN (14). The latter is synthesized in vitro, and it is deposited extracellularly as a fine network (15,16); it is broadly expressed in connective tissues, and it is particularly abundant in blood vessels, skin, heart, lung, kidney, and cornea (17)(18)(19). EMILIN is found at the interface between amorphous elastin and microfibrils (14), and it might regulate the formation of the elastic fiber given the finding that elastin deposition in vitro is perturbed by the addition of anti-EMILIN antibodies (14).…”
mentioning
confidence: 99%